Identification of Pyrolytic Oil Products by GC-MS Collected via Sodium Chloride (NaCl) Saturated Solution Extract - Norzahir, Sapawe; Muhammad Farhan, Hanafi (Elsevier Ltd., 2019)
In this study, the residual oil absorbed on spent bleaching clay (SBC) was pyrolyzed using tubular furnace to give pyrolytic oil also known as bio-oil which can be used as a chemical feedstock and others alternative fuel. A total oil adsorbed in SBC is 26.6 wt % which in agreement to total oil content in range of 17-35 %. Pyrolytic oil (bio-oil) gives aliphatic hydrocarbon range from C16-C44 via NaCl saturated solution extract. Carboxylic acids and alkanes were the major classes of products obtained. In addition, the presence of monoaromatic compounds, alkenes, alcohols, ketones, aldehydes, esters, nitrogenated compounds, and PAHs was also observed. The bio-oil products analyzed by GC-MS shows a good potential to be used as renewable fuels and chemicals. The pyrolysis of triglyceride materials to produce liquid hydrocarbon mixtures represents a process that has the potential to meet this need.